Mechanical, thermal, electrical and crystallographic behaviour of EPDM rubber/clay nanocomposites for out-door insulation applications. Issue 1 (2nd January 2020) - Rana, Ajay Singh; Vamshi, M. Kiran; Naresh, K.; Velmurugan, R.; Sarathi, R.
ABSTRACT: In this study, the degradation of tensile properties is investigated by placing the neat ethylene propylene diene monomer (EPDM) rubber and different weight percentages (2 wt%, 4 wt% and 6 wt%) of MMT clay dispersed in the EPDM rubber samples in a humidity chamber for 0, 5, 7, 12 and 14 days. The thermal properties of neat EPDM rubber and its clay nanocomposites were studied by using different instruments, namely dynamic mechanical analyser (DMA), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The viscoelastic properties are studied over the temperature range of −80°C to 80°C at different frequencies by using DMA. An increase in storage modulus and the decrease in loss tangent values are observed with the increase in clay content from 0 wt% to 6 wt% in EPDM rubber. Increase in storage modulus and glass transition temperature (Tg ) values is observed with the increase in frequency from 1 Hz to 50 Hz. Also, the thermal stability and change in mass of these materials as a function of temperature and time are studied using TGA. It is found that EPDM/4 wt% clay composites exhibit the highest residual weight at 690°C while neat EPDM exhibits the highest weight loss compared to samples dispersed with other clay weight percentages. Using X-ray diffraction (XRD), 2θ value was measured and the crystal structure is investigated. Fourier transformed infrared spectroscopy (FTIR) was used to characterise the grafting of clay in the EPDM rubber. The dielectric constant and conductivity were studied for different frequencies and temperatures.